Postgraduate Student Throuhput at the University of Ghana - Botha, RJ Nico (European Scientific Journal, ESJ, 2017)
A common thread in contemporary research on student throughput trends at higher education institutions refers to the ways in which the various stakeholders at institution of higher learning institutions take important decisions to ensure a better completion rate (throughput) among postgraduate students. To promote further appreciation of throughput among postgraduate students, this paper, based on an empirical study among a number of postgraduate students at the University of Ghana, reviews some trends and possible factors that might play a role in postgraduate student throughput at this university. The outcomes of this study show that student throughput at this institution has decreased over time due to financial difficulties; personal challenges; less opportunity for students to get study leave from their employers; and so forth. The paper concludes with recommendations to improve student throughput at postgraduate level. Among these recommendations is that they go for academic counselling before enrolling for postgraduate studies; and that a postgraduate fund be established to assist them financially.